Does the dural resection bed need to be irradiated? Patterns of recurrence and implications for postoperative radiotherapy for temporal lobe gliomas. Issue 2 (4th November 2020) - Teyateeti, Achiraya; Geno, Connie S; Stafford, Scott S; Mahajan, Anita; Yan, Elizabeth S; Merrell, Kenneth W; Laack, Nadia N; Parney, Ian F; Brown, Paul D; Jethwa, Krishan R
Abstract: Background: Patterns of recurrence and survival with different surgical and radiotherapy (RT) techniques were evaluated to guide RT target volumes for patients with temporal lobe glioma. Methods and Materials: This retrospective cohort study included patients with World Health Organization grades II to IV temporal lobe glioma treated with either partial (PTL) or complete temporal lobectomy (CTL) followed by RT covering both the parenchymal and dural resection bed (whole-cavity radiotherapy [WCRT]) or the parenchymal resection bed only (partial-cavity radiotherapy [PCRT]). Patterns of recurrence, progression-free survival (PFS) and overall survival (OS) were evaluated. Results: Fifty-one patients were included and 84.3% of patients had high-grade glioma (HGG). CTL and PTL were performed for 11 (21.6%) and 40 (78.4%) patients, respectively. Median RT dose was 60 Gy (range, 40-76 Gy). There were 82.4% and 17.6% of patients who received WCRT and PCRT, respectively. Median follow-up time was 18.4 months (range, 4-161 months). Forty-six patients (90.2%) experienced disease recurrence, most commonly at the parenchymal resection bed (76.5%). No patients experienced an isolated dural recurrence. The median PFS and OS for the PCRT and WCRT cohorts were 8.6 vs 10.8 months ( P = .979) and 19.9 vs 18.6 months ( P = .859), respectively. PCRT was associated with a lower RT dose to the brainstem, optic, and ocular structures, hippocampus, and pituitary. Conclusion: We identified no isolated dural recurrence and similar PFS and OS regardless of postoperative RT volume, whereas PCRT was associated with dose reduction to critical structures. Omission of dural RT may be considered a reasonable alternative approach. Further validation with larger comparative studies is warranted.